If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(5x-22)=(3x+10)
We move all terms to the left:
(5x-22)-((3x+10))=0
We get rid of parentheses
5x-((3x+10))-22=0
We calculate terms in parentheses: -((3x+10)), so:We get rid of parentheses
(3x+10)
We get rid of parentheses
3x+10
Back to the equation:
-(3x+10)
5x-3x-10-22=0
We add all the numbers together, and all the variables
2x-32=0
We move all terms containing x to the left, all other terms to the right
2x=32
x=32/2
x=16
| -2s+6=-18+s | | 16x-33=14x-24 | | 2i+8=5i+2 | | 1=h+19 | | 2g−3=3 | | 16.7z=-11.16+16.1z | | 45=0.4x+10 | | -1/5(x-5)-9=7 | | 60.50x+.20=192.10 | | .20x+60.50=192.10 | | 17=23-q | | 10x-5=20x+5 | | 1/2x-7=5 | | 192.10=60.50+.20x | | 15q=13 | | 8p-5p-15=6p-3 | | 17=16t+1 | | -18.68-0.2f=-2.8f+19.6+4.8f | | 60.50+.20x=192.10 | | 12+x=-8+6x | | 7x+4-3x+3=X | | 3+8-4x=3x+(-x)-7 | | 98.4=8(m+3.9) | | 3×n+18=36 | | 15-s=3+52.50 | | (6x+10)=(2x+50) | | -15.02+9.4k=11.4k+19.58 | | 1=2h+5 | | 2(2x+30+x=3x+18 | | n+3=8+4 | | 35+5n=-2(1+-7n) | | 3x+5+2x=-3+3x |